Comparative study of social sustainability between Western cities and Iranian historical cities - Safa Salkhi Khasraghi; Asma Mehan; Atefeh Hakimi Oskui (Journal of Architecture and Urbanism, 2024)
This study compares the social sustainability models of Western cities with those of historical Islamic cities in Iran, exploring their theoretical foundations and practical implementations. The research investigates whether the principles underlying Iranian Islamic cities align with Western standards of social sustainability, identifying similarities and differences between these models. Using a comparative analysis and an interpretative-historical approach, the study reviews the evolution of sustainable practices in both contexts. Concrete examples from Western urban models and Iranian cities are examined to assess their effectiveness in fostering sustainable communities and promoting sustainable behaviors. The findings highlight significant parallels between Western and Iranian Islamic models, with an 83% overlap, particularly with the new urbanism models of Europe and America, despite distinct approaches rooted in cultural and historical contexts. The study concludes that modern urbanism in the West and the Safavid era cities in Iran represent the most sustainable models within their respective regions.